2014
DOI: 10.1515/hmbci-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine control of satiation

Abstract: Abstract:Eating is a simple behavior with complex functions. The unconscious neuroendocrine process that stops eating and brings a meal to its end is called satiation. Energy homeostasis is mediated accomplished through the control of meal size via satiation. It involves neural integrations of phasic negative-feedback signals related to ingested food and tonic signals, such as those related to adipose tissue mass. Energy homeostasis is accomplished through adjustments in meal size brought about by changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 319 publications
(361 reference statements)
0
7
0
1
Order By: Relevance
“…Noradrenaline has been known for its role in the pathogenesis of anxiety ( Kalk et al, 2011 ; Zheng et al, 2019 ) and depression ( Seki et al, 2018 ) for a long time. Interestingly, it appears NE also controls satiation ( Asarian and Bachler, 2014 ). In addition, it has been reported that the microbiota influenced NE level in the gut lumen of mice ( Asano et al, 2012 ), but whether the bacteria produce NE to alter behavior through an indirect path was not determined.…”
Section: Neurotransmitter Modulation and Behavioral Outcomes Identifimentioning
confidence: 99%
“…Noradrenaline has been known for its role in the pathogenesis of anxiety ( Kalk et al, 2011 ; Zheng et al, 2019 ) and depression ( Seki et al, 2018 ) for a long time. Interestingly, it appears NE also controls satiation ( Asarian and Bachler, 2014 ). In addition, it has been reported that the microbiota influenced NE level in the gut lumen of mice ( Asano et al, 2012 ), but whether the bacteria produce NE to alter behavior through an indirect path was not determined.…”
Section: Neurotransmitter Modulation and Behavioral Outcomes Identifimentioning
confidence: 99%
“…Future studies with larger samples will be required to further explore the relationship between central nervous 5-HT and NPY in humans. Literature also suggests that the AA Leucine might also be involved in the regulation of appetite [ 44 ]; however, its relationship with NPY remains poorly understood. Given that Leucine was a compound of the ATD challenge, further investigation of how Leucine may impact on NPY levels may also benefit the current investigation of how central nervous 5-HT may be related to levels of NPY through the use of the ATD/BAL method.…”
Section: Discussionmentioning
confidence: 99%
“…One particularly important area of research is in satiety hormones, which are secreted by the GI tract in response to nutrients to help terminate meals. Since impairments in satiety have been associated with overeating in [67]. CCK is released by L cells of the intestine in response to lipids and proteins, and CCK has numerous postprandial functions, including decreasing appetite, slowing gastric emptying, and increasing gall bladder stimulation [68].…”
Section: Binge Eating In Bn and Bed Neuroendocrinementioning
confidence: 99%